Robust fault diagnosis and fault‐tolerant control for uncertain multiagent systems. (19th September 2020) - Yao, Lina; Wu, Yawei
Summary: This article considers the problem of fault diagnosis and fault‐tolerant control for uncertain multiagent systems. First, the multiagent system model with disturbances and uncertainty parameters is shown in the article. Then, a new robust adaptive observer based on relative estimation error is used to estimate actuator faults and the parameters of the observer can be obtained by solving the proposed linear matrix inequality. After the fault estimation information is obtained, a robust output feedback fault‐tolerant control algorithm based on fault estimation is proposed and the condition that the controller parameters need to be satisfied is given. Finally, the multiagent system with four aircrafts is used as an example to further prove the effectiveness of the algorithm proposed in this article.